Cost-effectiveness of Transcendental Meditation (TM) for treating Post-Traumatic Stress Disorder (PTSD) - Erik J. Groessl; Thomas R. Rutledge (PLoS ONE, 2025)
Objective A recent trial found that Transcendental Meditation (TM) was an effective non-trauma focused treatment for veterans with Post-Traumatic Stress Disorder (PTSD). The objective of this analysis was to examine the cost-effectiveness of TM for PTSD based on the trial results. Methods Between 2013–2017, 203 veterans with PTSD were randomized to either TM, Prolonged Exposure (PE), or to a PTSD health education (HE) control. Each group received 12 treatment sessions over 12 weeks. Results indicated that TM was non-inferior to PE for improving PTSD outcomes and both TM and PE were superior to HE, as hypothesized. The proportion of participants with a clinically significant improvement on the CAPS (≥10 point reduction) were TM = 61%, PE = 42%, and HE = 32%. A Markov model was developed to estimate the cost-effectiveness of TM, using the trial effectiveness data. Intervention costs, health care costs, and health utility values associated with response and non-response were derived from scientific literature. Costs were viewed from an organizational perspective and a 5-year time horizon (20 3-month cycles). One-way and probabilistic sensitivity analyses were conducted. Results TM was the dominant treatment strategy over both PE and HE in the cost-effectiveness analysis. TM cost an estimated $1504/12 sessions while PE and HE cost $2,822 and $492, respectively. The higher health care costs associated with non-response to therapy offset intervention cost differences. Findings were robust to variability. Conclusion In summary, using data from a recent RCT, TM was found to both improve health outcomes and reduce total costs in this analysis. Based on these results, further effectiveness trials and wider adoption of TM should be considered.